The reef fish assemblage of a coral reef system in the southwestern Gulf of Mexico - Guillermo Horta-Puga; Aura Aletse Morales-Aranda; José Luis Tello-Musi (Revista Mexicana de Biodiversidad)
Reef fish species richness of the Veracruz Reef System National Park (VRSNP) in the SW Gulf of Mexico is well known. However, the knowledge of the assemblage structure and its spatial variability in the reef ecosystem is quite limited. For that purpose, 5 field surveys (2012-2015) were performed, using the stationary visual census method, at 10 selected reefs. The most important findings were: 116 reef species were recorded. Average total reef fish density (2.31 Ind/m2) is similar to the records for the Caribbean reefs in the 20th century. The top 5 most abundant species were: Chromis multilineata, Ocyurus chrysurus, Abudefduf saxatilis, Stegastes leucostictus, and Elacatinus jarocho. We found evidence of a spatial distribution pattern with 3 well-defined groups of reefs: (1) those near the city of Veracruz, (2) those near the outlet of the Jamapa River, and (3) those farther from the city. Higher fish densities are associated to both high hermatypic coral and low crustose coralline algae bottom covers. The assemblage structure of reef fishes is different at distinct geomorphological reef zones. As expected, with some differences in the species abundance order, the assemblage structure of reef fishes is similar at all coral reefs in the Gulf of Mexico.